An exploratory review of the role of research mediators in social science - Sebba, J (2013)
The need to justify public expenditure has increased the emphasis on impact of research. Identifying ways to maximise impact is a requirement of research funders and a concern of governments internationally. Researchers are expected to communicate findings clearly, make use of the media and influence politicians and administrators. Through an exploratory review of the social science literature, the role undertaken by research mediators who translate findings and use networks to influence policy and practice is identified. Definitions of research mediators, their functions, methods, influence on decision making and implications for increasing the impact of research evidence in policy making are discussed. © Policy Press 2013.